Developing a hybrid learning model based on Moodle e-learning in Linguistics course - Abdullah; Ahmad Talib; Iskandar (Center for Humanities and Innovation Studies, 2021)
This study aims to create a hybrid learning model, and Linguistics course instructional materials to improve students' language knowledge, theories, and skills, particularly in the English department. A research design and development process were used to construct the learning model and instructional materials. This research entails a lengthy process of determining the needs of students and developing Linguistics products or course material to improve students' capacity or skills in learning language through hybrid learning using a Moodle platform (e-learning). The participants in this study are English department students from Faculty of Languages and Literature, Universitas Negeri Makassar. The students in the English Education and Literature department served as the study's sample. The study's findings revealed a hint of a hybrid learning model based on Moodle e-learning, syllabus, Linguistics course design instructional material, and student’s worksheet activities or exercises. The creation of a Moodle-based hybrid learning model in the Linguistics course, which includes learning procedures and steps, teaching materials, and assessment of learning outcomes, is intended to improve student learning abilities, particularly in the English Department, which includes aspects of knowledge, attitudes, and skills under today's curriculum demands. The Linguistics course's teaching materials were built on a Moodle-based hybrid learning paradigm that adheres to active, interactive, and communicative learning concepts. In this learning, active, creative, and communicative learning strategies and techniques and flexible learning strategies and methods are extremely conceivable.